SPLANCHNIC VEIN THROMBOSIS IN THE MEDITERRANEAN AREA IN CHILDREN - Hanaa El-Karaksy; Mona El-Raziky (Mediterranean Journal of Hematology and Infectious Diseases)
Abdominal venous thrombosis may present as splanchnic venous thrombosis (SVT) (occlusion of portal, splenic, superior or inferior mesenteric veins) or Budd- Chiari Syndrome (BCS) (thrombosis of inferior vena cava and/or hepatic veins). The aim of this review is to report the scanty data available for splanchnic vein thrombosis in the South Mediterranean area. In one Egyptian study, the possible circumstantial risk factors for portal vein thrombosis were found in 30% of cases:  19% neonatal sepsis, 8.7% umbilical catheterization, 6% severe gastroenteritis and dehydration. Another Egyptian study concluded that hereditary thrombophilia was common in children with PVT (62.5%), the commonest being factor V Leiden mutation (FVL) (30%). Concurrence of more than one hereditary thrombophilia was not uncommon (12.5%). The first international publication on hepatic veno-occlusive disease (VOD) in Egypt was in 1965 in children who rapidly develop abdominal distention with ascites and hepatomegaly. This disease was more frequent in malnourished children coming from rural areas; infusions given at home may contain noxious substances that were hepatotoxic and Infections might play a role. VOD of childhood is rarely seen nowadays. Data from South Mediterranean area are deficient and this may be attributable to reporting in local medical journals that are difficult to access. Medical societies concerned with this topic could help distribute this information.